Wnt/β-catenin-YAP axis in the pathogenesis of primary intraosseous carcinoma NOS, deriving from odontogenic keratocyst - Nakako, Yusuke; Hasegawa, Kana; Fujii, Shinsuke; Kami, Yukiko; Sakamoto, Taiki; Sakamoto, Mizuki; Moriyama, Masafumi; Kurppa, Kari J.; Heikinheimo, Kristiina; Yoshiura, Kazunori; Kawano, Shintaro; Kiyoshima, Tamotsu (Elsevier, 2025)
Odontogenic tumors (OGTs), which originate from cells of odontogenic apparatus and their remnants, are rare entities. Primary intraosseous carcinoma NOS (PIOC), is one of the OGTs, but it is even rarer and has a worse prognosis. The precise characteristics of PIOC, especially in immunohistochemical features and its pathogenesis, remain unclear. We characterized a case of PIOC arising from the left mandible, in which histopathological findings showed a transition from the odontogenic keratocyst to the carcinoma. Remarkably, the tumor lesion of this PIOC prominently exhibits malignant attributes, including invasive growth of carcinoma cell infiltration into the bone tissue, an elevated Ki-67 index, and lower signal for CK13 and higher signal for CK17 compared with the non-tumor region, histopathologically and immunohistopathologically. Further immunohistochemical analyses demonstrated increased expression of ADP-ribosylation factor (ARF)-like 4c (ARL4C) (accompanying expression of β-catenin in the nucleus) and yes-associated protein (YAP) in the tumor lesion. On the other hand, YAP was expressed and the expression of ARL4C was hardly detected in the non-tumor region. In addition, quantitative RT-PCR analysis using RNAs and dot blot analysis using genomic DNA showed the activation of Wnt/β-catenin signaling and epigenetic alterations, such as an increase of 5mC levels and a decrease of 5hmC levels, in the tumor lesion. A DNA microarray and a gene set enrichment analysis demonstrated that various types of intracellular signaling would be activated and several kinds of cellular functions would be altered in the pathogenesis of PIOC. Experiments with the GSK-3 inhibitor revealed that β-catenin pathway increased not only mRNA levels of ankyrin repeat domain1 (ANKRD1) but also protein levels of YAP and transcriptional co-activator with PDZ-binding motif (TAZ) in oral squamous cell carcinoma cell lines. These results suggested that further activation of YAP signaling by Wnt/β-catenin signaling may be associated with the pathogenesis of PIOC deriving from odontogenic keratocyst in which YAP signaling is activated.